Pengelolaan Pendapatan Asli Desa Sebagai Landasan Pembangunan Ekonomi Pedesaan - Komang Adi Kurniawan Saputra; Putu Budi Anggiriawan; A.A. Ayu Erna Trisnadewi; Putu Gede Wisnu Permana Kawisana; L.G.P. Sri Ekajayanti (Ekuitas: Jurnal Pendidikan Ekonomi, 2019)
This research was conducted to find out the management of village original income in Kerobokan Village and the role of BUMDes to be able to increase village original income and rural original income management strategy to improve the economy. This research method is qualitative descriptive method. Data obtained through in-depth interviews, observations and document studies are then analyzed by data reduction, data presentation, data analysis and conclusion. The result of the research shows that the management done by Kerobokan Village Government is in accordance with the management procedure, BUMDes play a role in increasing the village's original income so that the village government can carry out the development which impact on the village economy and the strategy implemented by the village government puts forward the coordination and cooperation.